Feminist consequences : theory for the new century - Bronfen, Elisabeth; Kavka, Misha (Gender and culture., 2001)
Exploring the status of feminism in this'postfeminist'age, this sophisticated meditation on feminist thinking over the past three decades moves away from the all too common dependence on French theorists and male thinkers and instead builds on a wide-ranging body of feminist theory written by women.